Pedagogical Bases of Teaching Physics - Atoeva Mehriniso Farhodovna; Karshiboyev Shavkat; Absalyamova Ilmira Ildarovna; Ubaydullayeva Vazira Patchaxanovna (Zien Journals, 2023)
This article discusses pedagogical aspects and features of teaching physics. It is reflected in the presence of specific features of teaching various divisions of the Physics
Keywords: pedagogy; pedagogical methods; lecture; lessons